Identifying the Urgency of Indonesia's Nickel Industry Downstream: WTO Dispute and Global Momentum [Identifikasi Kepentingan Hilirisasi Industri Nikel Indonesia: Sengketa WTO dan Momentum Global] - Pattinussa, Jhon Maxwell Yosua (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2024)
In recent years, Indonesia has been striving to vertically integrate its nickel industry. The primary reasons for this are technological advancements, the global momentum towards sustainability, and abundant nickel mineral resources. With 52% of the world's nickel reserves, Indonesia has undertaken the downstream policy of its nickel industry. Various policies have been created and implemented, including laws, government regulations, and ministerial regulations, to guide the downstream process. However, the European Union's lawsuit against Indonesia at the WTO has posed a significant challenge to this process. After being found guilty, Indonesia has appealed the EU's lawsuit. This research aims to identify the current state of the downstream process and the underlying interests behind Indonesia's ongoing appeal. Using qualitative research methods and focusing on explaining the downstream of the national nickel industry, this study seeks to uncover and elucidate the main agenda behind the urgency of Indonesia's nickel industry downstream amid the WTO dispute and global momentum in electronic vehicle era. Bahasa Indonesia Abstract: Dalam beberapa tahun terakhir, Indonesia telah berupaya keras untuk mengintegrasikan industri nikel mereka secara vertikal. Alasan utama dibalik hal ini adalah kemajuan teknologi yang semakin pesat, momentum global yang semakin mengarah ke berkelanjutan, dan sumber daya mineral nikel yang berlimpah. Dengan memiliki 52% dari cadangan nikel dunia, Indonesia telah menjalankan hilirisasi dalam industri nikel mereka. Berbagai kebijakan telah dibentuk dan diimplementasikan untuk menuntun proses hilirisasi, termasuk aturan hukum, aturan pemerintah, dan regulasi tingkat menteri. Namun, tuntutan hukum Uni Eropa melawan Indonesia di WTO telah memberikan ancaman signifikan terhadap proses ini. Setelah divonis bersalah, Indonesia telah mengajukan banding terhadap tuntutan hukum Uni Eropa tersebut. Penelitian ini bertujuan untuk mengidentifikasi situasi terkini dari proses hilirisasi dan kepentingan tersembunyi di balik banding Indonesia yang sedang berjalan. Dengan menggunakan metode penelitian kualitatif dan berfokus pada menjelaskan hilirisasi dari industri nikel nasional, penelitian ini mencoba mengungkapkan dan menjelaskan agenda utama di balik urgensi hilirisasi industri nikel Indonesia yang berkaitan dengan sengketa WTO dan momentum global di era kendaraan listrik.